Realization of current-mode fully integrated full-wave rectifier - Basak, Muhammed Emin; Kacar, Firat (ELSEVIER GMBH, 2017)
In this paper, a new fully integrated high frequency current-mode full-wave rectifiers are presented. The proposed circuits rectify the input signals without diode, so the output signal confronts zero-crossing distortions because of the diode characteristics have been solved with this rectifier even in high frequencies. While the current rectifier has dual output, the voltage rectifier has one output. The presented circuits have a vastly superior zero crossing performance, good linearity, minimum number of transistors, wide frequency range, and they are suitable for monolithic integrated implementation. The performances of the proposed circuits are investigated through LTSpice. Monte-Carlo and Noise analyses have also been performed to show the effectiveness of the proposed circuits. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Full-wave rectifier; High frequency; Precision rectifier; Current-mode; WIRELESSLY POWERED DEVICES; LOW-FREQUENCY APPLICATIONS; VOLTAGE CMOS RECTIFIER; HARVESTING APPLICATIONS; ACTIVE RECTIFIER; STANDARD CMOS; ENERGY; RECTIFICATION; CONVEYORS; CIRCUITS; Engineering; Telecommunications